2012
DOI: 10.3758/s13423-011-0214-6
|View full text |Cite
|
Sign up to set email alerts
|

Increasing interletter spacing facilitates encoding of words

Abstract: Recent research has suggested that words presented with a slightly increased interletter spacing are identified faster than words presented with the default spacing settings (i.e., is faster to identify than ; see Perea, Moret-Tatay, & Gomez, 2011). To examine the nature of the effect of interletter spacing in visual-word recognition (i.e., affecting encoding processes vs. quality of information), we fitted Ratcliff's (1978) diffusion model to a lexical decision experiment in which we manipulated a range of fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 28 publications
7
61
3
Order By: Relevance
“…While it is clear that increasing intraword spacing beyond some critical value (two or three character spaces) will disrupt reading, it is far less clear what effect will occur for more subtle increases. There are reports of facilitation in lexical decision tasks with subtle increases to intraword space (Perea & Gomez, 2012). However, as Perea, Moret-Tatay, and Gomez (2010) noted, the results of studies that use subtle manipulations of increased intraword spacing are somewhat inconsistent, probably due to the fact that the amount of space added between letters varied across the studies, as did the fonts used in the studies.…”
Section: Intraword Spacing Effectsmentioning
confidence: 73%
See 1 more Smart Citation
“…While it is clear that increasing intraword spacing beyond some critical value (two or three character spaces) will disrupt reading, it is far less clear what effect will occur for more subtle increases. There are reports of facilitation in lexical decision tasks with subtle increases to intraword space (Perea & Gomez, 2012). However, as Perea, Moret-Tatay, and Gomez (2010) noted, the results of studies that use subtle manipulations of increased intraword spacing are somewhat inconsistent, probably due to the fact that the amount of space added between letters varied across the studies, as did the fonts used in the studies.…”
Section: Intraword Spacing Effectsmentioning
confidence: 73%
“…Therefore, it is possible that the spacing manipulation we employed in Experiment 1 would affect these two fonts differently. An added benefit of using Times New Roman is that this is the font used by Perea et al (2010) and Perea and Gomez (2012), who found facilitation with increased intraword spacing in single-word recognition.…”
Section: Methodsmentioning
confidence: 99%
“…Perea & Gomez, (2012a) varied interletter spacing from -0.5 points to +1.5 points and found a linear decrease in RT. Further, using the diffusion model (Ratcliff, 1978;Ratcliff, Gomez, & McKoon, 2004), they were able to simulate the effect of spacing as an early encoding process.…”
Section: Small Letter-spacing Manipulationsmentioning
confidence: 97%
“…That is, the reading cost of easy-to-read handwritten stimuli relative to printed stimuli cannot be solely due to an early letter-encoding component. As indicated in the Introduction, if the effect of script had only occurred in an early encoding (nondecisional) component, there should have been a shift in the RT distributions and little/no effect in the error rates (see Gomez & Perea, 2014;Perea & Gomez, 2012, for instances of such effects). However, there was a change in the shape of the RT distributions (i.e., the slower condition also showed more positive asymmetry), and this was accompanied by more errors to handwritten stimuli than to printed stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…Analyses on the RT distributions provide more constraining information on the nature of the effects under scrutiny than the analyses on the mean RTs (Ratcliff, Gomez, & McKoon, 2004; see also Gomez, Perea, & Ratcliff, 2013;Perea, Abu Mallouh, & Carreiras, 2013;Perea, Vergara-Martínez, & Gomez, 2015). First, an effect that only affects the early encoding (non-decisional) components of visual word recognition should produce changes in the mean RTs and are reflected as a shift of the RT distributions (i.e., similar magnitude of the effect across quantiles; e.g., identity vs. unrelated condition in masked priming; see Gomez et al, 2013;Perea, Vergara-Martínez, & Gomez, 2015; inter-letter spacing; Perea & Gomez, 2012;rotated words: Gomez & Perea, 2014). Second, an effect that affects the "quality of information" in a decision stage of the lexical decision task should produce not only changes in the mean RTs but also changes in the shape of the RT distributions (i.e., a greater magnitude of the effect in the higher quantiles than at the leading edge of the RT distribution) and more errors in the slower condition (e.g., the word-frequency effect; see Ratcliff et al, 2004).…”
mentioning
confidence: 99%